KAZAKHSTAN-CHINESE COOPERATION IN THE ENERGY SPHERE - ESIMOVA, Kalamkas (CENTRAL ASIA AND THE CAUCASUS, 2005)
Relations with the PRC is a priority area in our republic’s foreign policy. This is not just because we are neighbors, but also because Beijing has enormous economic potential, as well as immense influence on the international arena. China was among the first states to recognize Kazakh stan’s sovereignty. These countries began to devel op multifaceted bilateral cooperation from the moment diplomatic ties were established in January 1992. Cooperation in the energy sphere began in 1997, when the Chinese National Petroleum ComPany (CNPC) became a shareholder of the Aktobe munaigaz Company (60.3%). (An agreement on cooperation in the oil and gas sphere was signed by the governments of both countries in September. At that time, the Kazakhstan Ministry of Energy and Mineral Resources and the CNPC signed a general agreement on developing fields in Kazakhstan and building an oil pipeline from Kazakhstan to China.) Today, cooperation in the energy sphere is developing successfully and becoming the pivot of Kazakhstani-Chinese relations, which was emphasized in particular during Kazakhstan President Nursultan Nazarbaev’s visit to the PRC in May 2004. But joint work in this area did not get off to a smooth start. Delays in laying the West Kazakh stan-West China oil pipeline kept economists and political scientists in a state of tension. Many forecasts of its prospects have been made over the years, but they were all very pessimistic, no one believed the route would ever come to fruition. Mainly because it is economically inefficient, and the Kazakh stan side will not be able to fully load the pipeline, which is too long anyway. The low quality of Kazakhstani oil, which requires additional refining, thus raising its net cost, was also among these pessimistic arguments. So many experts decided that the intentions to build this pipeline were merely a political step and Beijing’s arrival on Astana’s oil and gas market was dictated to a certain extent by geopolitical considerations. At that time, many believed that the main stimulus behind transporting oil was not economic expediency but exerting in fluence in the region. However, the decisive steps taken by both sides in 2004 to implement this project, as well as the fact that construction of the Atasu-Alashankou line actually began, refuted all these arguments. Now political scientists are looking for the true rea sons for the keen attention being shown what would seem to be an already frozen project and which many called unrealistic. In our opinion, it was revived for several reasons, including those not related to Kazakhstani, but to Russian oil, or to be more precise, to pumping it along the Angarsk-Daqin pipeline, which would be more economically preferable for the Chinese. First, because the Russian side is always putting off its construction, second, partly due to the recent events involving YUKOS, No. 1(31), 2005 and third, due to failure of the transaction between the PRC and the Slavneft Company. The anti-Chinese moods in the RF State Duma and among ordi nary Russians also had an important role to play here. The “theory of the Chinese threat” is current ly very popular in Russia, and Moscow does not want the Chinese economy to become any strong er. Nor is Kazakhstan entirely free of Sinophobia, although now it has subsided, whereby it was nev er as rampant in our country as it was in Russia. Even in the Kazakhstan mass media, where it was a hot topic for a while, it has now essentially disap peared into oblivion. Incidentally, Beijing is also very concerned about the “theory of the Chinese threat,” with respect to which Deputy PRC Foreign Minister Liu Guchang particularly stressed the need to raise political trust between the countries. Another reason for reviving the pipeline project from Kazakhstan to China is the PRC’s concern about the U.S.’s actions in the Middle East. Speaking at an international forum on China’s eco nomic strategy (Beijing, 21-23 May, 2004), Professor Fang Zhangping, an employee of the Research Center of International Energy Strategy, stated: “The events in Iraq graphically show that the Unit ed States, as the first oil importer in the world, will try to ensure its direct presence in the regions where oil is produced, which could pose a threat to China’s increase in oil import.” 1 That is, the PRC’s serious concern about its oil security was probably one of the reasons the Celestial Kingdom decided to create strategic oil supplies. Of course, since its accelerated economic growth rates require increasingly larger amounts of energy resources, creating these supplies becomes extremely problematic. This is probably why China decided to step up its cooperation with Kazakhstan and Russia in order to safeguard against any possible boycott on deliveries of Middle Eastern oil. In this context, Beijing’s desire to begin building the “forgotten” pipeline as soon as possible does not look so sudden and strange. What is more, according to some researchers, an important component of the oil security strategy for China is the “go abroad” (zouchuqu) slogan, which implies, among other things, participating in the development of foreign oil fields using Chinese technology and Chinese capital. As Ya. Berger believes this slogan is aimed primarily at the countries neighboring on the PRC. In his book On Chi na’s Energy Strategy, he presents the following quote from an article by Xia Yishan, “The Situation in China’s Energy Sector and its Development Strategy,” published in the newspaper Renmin rib ao: “Russia, Kazakhstan, and the Central Asian states have rich oil and gas resources, are friendly neighbors, and have relative political stability, so, from the viewpoint of long-term prospects, the cent er of gravity should be here.” 2